Urban Herpetofauna: A Case Study in Ujjain City of Central India - Ingle, Mukesh; Yadav, Ulka; Bhilala, Ashok K.; Pawar, Manohar (International Journal of Scientific Research in Biological Sciences, 2019)
This paper presents a herpetofaunal inventory of the urban city of Ujjain, Madhya Pradesh along with major threats existing in the study area, snake-human conflict and conservation steps taken. Herpetofaunal population in degraded while urban habitat is essential for their long term conservation measures. A total of 39 species of reptiles and amphibians representing 15 families were detected with special account of Argyrogena fasciolata, Wallophis brachyurus, Lycodon aulicus, Ptyas mucosa, Xenochrophis piscator, and Lygosoma lineatum. Snakes were the most collected reptilian species, while Amphibians comprised the little group of the sample. Reptile Conservation & Research Centre is established in the city by Sarpa Anusandhan Sangthan to minimize the snake-human conflict and to educate and familiarise people with them